2013
DOI: 10.1002/phar.1167
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring: Recent Evidence and Clinical Pharmacy Applications

Abstract: Conventional office blood pressure readings are a well-established surrogate for the prediction of cardiovascular risk. It is assumed that these readings reflect an underlying average level of blood pressure exposure occurring in an individual over a period of time. But because blood pressure is not static, important additional prognostic information about the diurnal blood pressure profile, including within-day and between-day variability, is not easily ascertained from conventional measurements. Ambulatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Previous research has highlighted opportunities for clinical pharmacists to adopt a role in supporting the use of blood pressure home measuring monitors [20]. Pharmacists are in a pivotal position for providing pharmaceutical care services including measurements of blood pressure, education on the medical condition and medication use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has highlighted opportunities for clinical pharmacists to adopt a role in supporting the use of blood pressure home measuring monitors [20]. Pharmacists are in a pivotal position for providing pharmaceutical care services including measurements of blood pressure, education on the medical condition and medication use.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the pharmacist was identified as the health care professional to counsel patients on the proper use of the blood pressure home measuring monitors (56 %), followed by the specialist. We recommend collaborative practice models between pharmacists and physicians as they have been found to optimize medication management and lead to improvements in hypertension outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant differences between PP tertiles for the relative treatment effect in the current study could be the result of a type 2 error. Further, a categorization of PP based on standard BP measurements may be inferior in comparison to 24‐hour and central pressure measurements . In the ACCOMPLISH trial, the difference in SBP between the two treatment groups was <1 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory blood pressure monitoring is considered the best method for confirming an office-based hypertension diagnosis [21] because of its strong predictive ability of future cardiovascular risk [22][23][24] and its ability to better describe blood pressure variability [25]. This method is better at identifying individuals with white-coat hypertension [25] and is well received among patients [26][27][28].…”
Section: Introductionmentioning
confidence: 99%